The Oxford digital multiple errands test (OxMET): Validation of a simplified computer tablet based multiple errands test. Issue 6 (3rd July 2022) - Webb, Sam S.; Jespersen, Anders; Chiu, Evangeline G.; Payne, Francesca; Basting, Romina; Duta, Mihaela D.; Demeyere, Nele
ABSTRACT: Impairments in executive functioning are common following Acquired Brain Injury, though there are few screening tools which present a time efficient and ecologically valid approach to assessing the consequences of executive impairments. We present the Oxford Digital Multiple Errands Test (OxMET), a novel and simplified computer-tablet version of a Multiple Errands Test. We recruited 124 neurologically healthy controls and 105 stroke survivors to complete the OxMET task. Normative data and internal consistency were established from the healthy control data. Convergent and divergent validation was assessed in a mixed subset of 158 participants who completed the OxMET and OCS-Plus. Test–retest reliability was examined across a mixed subset of 39 participants. Finally, we investigated the known-group discriminability of the OxMET. The OxMET demonstrated very high internal consistency, and stable group level test–retest performance as well as good convergent and divergent validity. The OxMET demonstrated high sensitivity and good specificity in overall differentiation of stroke survivors from controls. The Oxford Digital Multiple Errands Test is a brief, easy to administer tool, designed to quickly screen for potential consequences of executive impairments in a virtual environment shopping task on a computer tablet. Initial normative data and validation within a chronic stroke cohort is presented.